ZAKAT FITRAH BAGI JANIN YANG MASIH DALAM ANDUNGAN MENURUT IBNU HAZM - Ayi Ishak Sholih Muchtar; Siti Nurlaela (Istinbath | Jurnal Penelitian Hukum Islam, 2018)
One of the pillars of Islam related to the matter of treasure is zakat. Zakat is divided into two, namely zakat mal and zakat fitrah. In the zakat mâl, humans menzakati treasure or opinion such as gold, silver, animals, plants and commercial goods with clear conditions (Muslims, freedom, property is perfect, nishab and haul). While zakat fitrah different from zakat mâl, because the dizakati are human (self or soul) not a wealth or income. In the matter of zakat fitrah, the scholars are different pendapa about the obligation of zakat for the fetus that is still in the womb. Jumhur ulama argue that does not obligate zakat fitrah for the fetus that is still in the womb. While the fuqaha Dzahiri argues that zakat fitrah is obligatory for the fetus who is still in the womb when it has been perfect one hundred and twenty days in the mother's belly before the dawn on the night of Eid al-Fitr.